THE IMPACT OF THE REVOCATION OF PERMENPORA NO. 14 OF 2024 ON SPORTS PERSONNEL ON THE DEVELOPMENT OF SPORTS ACHIEVEMENTS IN NORTH SUMATRA - Dicky Hendrawan; Eka Abdurrahman; Brema Bangun; Irfandi Irfandi (Jurnal Penjaskesrek, 2025)
Permenpora Number 14 of 2024 has caused controversy since it was passed because several norms in it are considered to have the potential to interfere with the autonomy of national sports organizations and are contrary to the principles of the Olympic Charter. The government then revoked the regulation through Permenpora Number 7 of 2025. This article analyzes the impact of the revocation of Permenpora 14/2024 on sports people, especially on the development of sports achievements in North Sumatra Province. Using a qualitative-descriptive approach that combines the analysis of regulatory documents, literature review, and the review of stakeholder responses (media, regional associations, KONI), this article finds that revocation produces multi-layered effects: (1) reducing institutional tensions and legality concerns among sports administrators and KONI, (2) restoring the practice of organizational autonomy that is seen as important for long-term coaching, (3) raising the need for regulatory revision Internal management and clarification of relations between the central and regional governments, and (4) opening momentum for more participatory regulatory reform. In North Sumatra, local responses show appreciation as well as implementation challenges: improving coaching coordination, human resource and budget arrangement, and the need to strengthen organizational capacity at the provincial and district/city levels. This article recommends four policy steps to minimize short-term negative impacts and maximize opportunities to improve governance of sports achievement coaching in North Sumatra. The primary sources underlying the analysis came from the Permenpora 14/2024 document, the revocation document (Permenpora 7/2025), and the news and stakeholder statements.